2022
DOI: 10.1159/000525598
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid and Intraventricular Hemorrhage in a Patient with a Pure Arterial Malformation and Two Associated Aneurysms in the Posterior Inferior Cerebellar Artery: A Case Report and Literature Review

Abstract: Introduction Pure arterial malformations (PAMs) are rare vascular abnormalities defined as dilated, tortuous arterial loops without any associated venous compartment. PAMs are thought to be benign developmental anomalies that can be safely managed conservatively. Methods We present a case of life-threatening hemorrhage in a patient with a PAM associated with two aneurysms and review the literature describing hemorrhages associated with PAMs. Results A 65-year-old female presented with subarachnoid and intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…One report has suggested that PAMs are associated with aneurysms in nearly half of these patients. 6 Our literature review revealed that 14 of 50 reported PAM cases had an associated aneurysm, and of these patients with an aneurysm-associated PAM, 5 of 14 developed SAH/intracranial hemorrhage. Including the present case, 5 of 7 PAMs resulting in SAH had associated aneurysms, whereas 2 of 7 PAMs spontaneously caused SAH.…”
Section: Discussionmentioning
confidence: 88%
“…One report has suggested that PAMs are associated with aneurysms in nearly half of these patients. 6 Our literature review revealed that 14 of 50 reported PAM cases had an associated aneurysm, and of these patients with an aneurysm-associated PAM, 5 of 14 developed SAH/intracranial hemorrhage. Including the present case, 5 of 7 PAMs resulting in SAH had associated aneurysms, whereas 2 of 7 PAMs spontaneously caused SAH.…”
Section: Discussionmentioning
confidence: 88%
“… 11–17 Of the reported cases, the source of rupture was attributable to a pure arterial malformation vessel in two cases and an associated focal aneurysm in five cases. 11–17 The malformation was localized to the posterior circulation in five cases and anterior circulation in one case. 11 , 12 , 14–17 Interestingly, one case reported the coexistence of two pure arterial malformations in the anterior and posterior circulation.…”
Section: Discussionmentioning
confidence: 93%
“… 13 The majority of cases underwent intervention (six of seven cases). 11–16 Of the cases treated, surgical intervention (e.g., aneurysm clipping, clip trapping, bypass, parent artery occlusion) was pursued in five of six cases, whereas endovascular ethylene vinyl alcohol copolymer (Onyx) embolization was implemented in one case. 11–16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations